GLOBAL FINANCIAL CRISIS – STUMBLICK BLOCK OR OPPORTUNITY FOR BOSNIA AND HERZEGOVINA ON THE ROAD TO EUROPEAN UNION - Маријана П. Милић, M.Sc. (Acta Economica, 2009)
Utilization of global financial crisis as an opportunity for Bosnia and Herzegovina to appraise its position on a transformation path from centrallyplanned economy to market oriented economy within the signed agreement on Stabilization and Association (SAA) to EU has been discussed in this paper. Having in mind that a macroeconomic policy worsened, one of the greatest weaknesses of B&H has been presented, insufficient institutional development. By its resolving or strengthening may take B&H to more favorable position in comparison with other countries of Western Balkan, countries that signed SAA, in order to enable faster and safer road to the EU accession. By qualitative and quantitative methods the paper has been put in a wider contest using Global Competitive Index.